PENINGKATAN LITERASI FINANSIAL DAN KEPEDULIAN LINGKUNGAN MELALUI PROGRAM KKN DI SDN 1 PANAWANGAN - Nur Azizah, Tika; Azizah, Nur; Nurmala, Lala; Sekar Ayu Kinasih, Gendhys; Rudiansyah, Egi; Syamsul Hidayat, Eep; Liyana, Ayu; Andika Putra, Dika (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The Community Service Program (KKN) of Universitas Muhammadiyah Kuningan in Panawangan Village was implemented as a form of student engagement to strengthen financial literacy and environmental awareness among elementary school students. This program aimed to foster early saving habits while increasing awareness of plastic waste management. The activity was conducted on August 9, 2025, at SDN 1 Panawangan, involving 21 fourth-grade students (11 boys and 10 girls). The methods included a socialization session on the importance of saving, education on waste management, and a hands-on workshop creating piggy banks from used plastic bottles as a creative medium for saving. The results showed that all participants successfully produced 21 piggy banks and demonstrated high enthusiasm in understanding the concepts of saving and plastic waste recycling. This program not only enhanced students’ financial literacy but also instilled environmental responsibility through the application of recycling principles. It is expected that this KKN activity will inspire schools and communities to develop similar initiatives as a sustainable character-building effort.